Text and discourse: two suprasentential units - Castillo Pinto, Gloria (Contextos: Estudios de Humanidades y Ciencias Sociales, 2017)
The suprasentential units of text and discourse have become very important in modem linguistics, even though there exists some confusión about these concepts as well as some disagreement about the scope of the related disciplines of text linguistics and discourse analysis together with their theoretical and methodological dijferences. Some considerations about the nature and properties of both these units are made here because of their influence on the communicative approach to the teaching offoreign languages. Special attention is given to the phenomenon of cohesión, which is treated in depth by Halliday and Hasan (1976).